EFEKTIFITAS PEMBERIAN PENDIDIKAN KESEHATAN MELALUI MEDIA AUDIOVISUAL TENTANG KANKER SERVIKS TERHADAP PENGETAHUAN IBU RUMAH TANGGA (IRT) - Annisa " Mayanti; Sri " Utami; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract This research aims to determine the effectiveness of health education through audiovisual media about cervical cancer to the level of knowledge of housewives. Methodology on this research was a quasy Experiment with Non-Equivalent Control Group. The research was conducted at Rejosari subdistrict on Tenayan Raya district to 30 persons consist of 15 for experimental group and 15 for control group. This research were method used of purposive sampling. Measuring tool used is a questionnaire that has been tested for validity and reliability. The analysis used were univariate and bivariate analysis using t test-dependent and t test-independent. The results showed health education effective to increase knowledge of housewives about cervical cancer by audiovisual media (p value 0.002). Based on thisresearch was recommended to health agent for giving health education with audiovisual media to increase knowledge of housewives about cervical cancer. Keywords : audiovisual, cervical cancer, housewife, knowledge.